(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
This study explores the impact of information and communication technology (ICT) on social informatics, with a particular focus on Saudi Arabia and Jordan. The objective is to gain a comprehensive understanding of the utilization of Information and Communication Technology (ICT) in these countries and its impact on the outcomes of research. This qualitative study involved conducting in-depth interviews with individuals engaged in social informatics research, including researchers, professors, and professionals. The material acquired is subject to thematic evaluation in order to derive significant insights. The study’s findings reveal the emergence of several noteworthy patterns. The advent of information and communication technology has enabled scientists to analyze extensive databases, resulting in comprehensive and refined discoveries. The proliferation of internet usage in contemporary society has resulted in the emergence of a significant impediment known as the digital divide. Capacity development and training programs are deemed essential for researchers to optimize their utilization of ICT tools and approaches. It is emphasized that the optimal utilization of Information and Communication Technology (ICT) in social informatics research necessitates the imperative collaboration among academia, business, and government.